Pengurangan emisi dari sektor lahan: studi komparatif Indonesia dan Vietnam - Mukti, Abdul; Koestoer, Raldi Hendro (Jurnal Bisnis Kehutanan dan Lingkungan, 2023)
The increase in earth's surface temperature for 2001 - 2020 was 0.99oC with the highest increase in 2011 - 2000, namely 1.09oC, which was higher than 1850 - 1900. Awareness has emerged from several countries worldwide about the dangers of increasing GHGs due to climate change, so countries have gathered to discuss climate change at international conferences. This conference is known as the Conference of Parties (COP). The Indonesian government is committed to reducing carbon emissions by 29% independently and 41% with international assistance by 2030 so that the earth's temperature does not increase beyond 2°C. Vietnam ratified the Paris Agreement and committed unconditionally to reduce by 8% GHG emissions by 2030 relative to business as usual (BAU) levels and aims to achieve a 25% reduction subject to international support. This research aims to compare the policies of the Indonesian and Vietnamese governments to achieve land sector GHG emission reduction targets. This research will analyze Indonesia and Vietnam's policies, strategies, and implementation in reducing land sector emissions. The research method used was a qualitative approach.